Ideology in U.S. foreign relations : new histories - Nichols, Christopher McKnight; Milne, David, 1976- (Columbia University Press, 2022)
"Ideology drives American foreign policy in ways seen and unseen. Racialized notions of subjecthood and civilization underlay the political revolution of eighteenth-century white colonizers; neoconservatism, neoliberalism, and unilateralism propelled the post-Cold War United States to unleash catastrophe in the Middle East. Ideologies order and explain the world, project the illusion of controllable outcomes, and often explain success and failure. How does the history of U.S. foreign relations appear differently when viewed through the lens of ideology? This book explores the ideological landscape of international relations from the colonial era to the present. Contributors examine ideologies developed to justify-or resist-white settler colonialism and free-trade imperialism, and they discuss the role of nationalism in immigration policy. The book reveals new insights on the role of ideas at the intersection of U.S. foreign and domestic policy and politics. It shows how the ideals coded as "civilization," "freedom," and "democracy" legitimized U.S. military interventions and enabled foreign leaders to turn American power to their benefit. The book traces the ideological struggle over competing visions of democracy and of American democracy's place in the world and in history. It highlights sources beyond the realm of traditional diplomatic history, including nonstate actors and historically marginalized voices. Featuring the foremost specialists as well as rising stars, this book offers a foundational statement on the intellectual history of U.S. foreign policy"-- Provided by publisher.
Keywords: Ideology -- United States -- History.; Democracy.; United States -- Foreign relations -- Philosophy.; United States -- Politics and government -- Philosophy.; Idéologie -- États-Unis -- Histoire.; États-Unis -- Politique et gouvernement -- Philosophie.; POLITICAL SCIENCE -- International Relations -- General.; Democracy; Diplomatic relations -- Philosophy; Ideology; Politics and government; United States; History